The Effectiveness of Dual-Mode Simulation (Video and Puzzle) in Enhancing Flood Disaster Preparedness Among Elementary Students in Flood-Prone - Zulhijayanti, Zulhijayanti (Bantayang Omni Cendekia, 2024)
Background: Floods are the most common natural disasters in Indonesia, accounting for 43.1% of incidents in 2022. Flood-prone urban areas such as Makassar face recurrent seasonal inundations. Enhancing disaster preparedness through simulation-based education in schools is crucial. Objective: This study aimed to evaluate the effectiveness of dual-mode simulations (animated video and puzzle-based learning) in improving flood disaster preparedness among elementary school students. Methods: A pre-experimental one-group pretest-posttest design was used involving 84 students from SD Inpres Nipa-Nipa, Makassar. Interventions included video simulations and educational puzzles administered in two sessions over one month. Preparedness levels were measured using a validated questionnaire before and after the intervention.Results: Wilcoxon test results showed significant improvement in disaster preparedness after both video simulation (p = 0.000) and puzzle-based learning (p = 0.000).Conclusion: Dual-mode simulation methods significantly improved flood disaster preparedness in schoolchildren. Educational simulations, particularly when combined with interactive tools, are recommended for school-based disaster risk reduction strategies.